EpCAM-associated claudin-7 supports lymphatic spread and drug resistance in rat pancreatic cancer - Thuma, Florian; Zöller, Margot (International journal of cancer, 2013)
Pancreatic cancer has a dismal prognosis because of early metastatic spread, a suggested feature of cancer-initiating cells (CIC). To control for a functional contribution of the pancreatic CIC-marker EpCAM, we explored metastasis formation by a stable EpCAM-knockdown (ASML-EpCkd) of the rat pancreatic adenocarcinoma line BSp73ASML (ASMLwt). As EpCAM associates with claudin-7, an ASML-claudin-7-knockdown (ASML-cld7kd) was included to differentiate between EpC- and EpC-cld7-mediated effects. The metastatic capacity of ASML-EpCkd and more pronounced ASML-cld7kd cells is strikingly reduced. EpC-associated cld7 interferes with EpC-mediated cell-cell adhesion and supports migration. This requires cld7 phosphorylation and formation of an EpC-cld7-tetraspanin-alpha6beta4 complex in glycolipid-enriched membrane domains (GEM), where cld7 associates via the tetraspanin-alpha6beta4 complex with phosphorylated ezrin. The association of cld7 with alpha6beta4 and cytoskeleton strongly stimulates tumor cell migration. However, EpC does not actively contribute. Instead, GEM-located cld7 associates with presenilin-2, which facilitates EpC cleavage and thereby tumor cell proliferation. Finally, the EpC-cld7 complex promotes drug resistance. Both EpC and cld7 support MAPK and JNK activation, such that in ASML-EpCkd and ASML-cld7kd cells an undue expansion of proapoptotic molecules is observed. Only cld7 promotes activation of the PI3K/Akt pathway by a strong downregulation of Pten. Accordingly, cisplatin treatment prolongs the survival time of ASML-cld7kd-bearing rats. Taken together, cld7 supports tumorigenic features of EpC by provoking EpC cleavage and thereby its cotranscription factor activity. On the other hand, only cld7 is directly engaged in motility and apoptosis resistance. Thus, at least in concern of migrating CIC, it is cld7 that acts as a CIC biomarker.